Proceedings of the 1st International Conference on Sport Sciences, Health and Tourism (ICSSHT 2019) 2021
DOI: 10.2991/ahsr.k.210130.069
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypnobrithing Techniques on Reducing Anxiety of Third Trimester Mothers During Preparation for Childbirth

Abstract: Pregnancy is a natural thing that happens to women who are productive. During pregnancy there are changes in the mother both physically and psychologically. In Indonesia about 95% of health workers do not pay much attention to the psychological condition of women giving birth but rather pay attention to the physical condition of the mother and the baby being born. The delivery process has an impact on extreme pain and can cause fear and even death of both the mother and baby. One method that can be used is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This significant disparity in mean anxiety levels between the experimental (7.67) and control groups (12.07) not only underscores the efficacy of hypnobirthing interventions but also correlates with findings from Imannura et al, where hypnobirthing participants reported markedly lower anxiety levels compared to their non-participating counterparts (7). Moreover, the reduction of anxiety from medium to mild levels, as found in our study, mirrors the outcomes of similar research, reinforcing the assertion that hypnobirthing is a potent therapeutic approach for mitigating pregnancy-related anxiety (24). This claim is further corroborated by another study that noted a significant transition in pregnant women's anxiety levels from extremely high to normal post a 12-week hypnobirthing regimen, emphasizing the profound psychological benefits of this therapy (25).…”
Section: Discussionsupporting
confidence: 91%
“…This significant disparity in mean anxiety levels between the experimental (7.67) and control groups (12.07) not only underscores the efficacy of hypnobirthing interventions but also correlates with findings from Imannura et al, where hypnobirthing participants reported markedly lower anxiety levels compared to their non-participating counterparts (7). Moreover, the reduction of anxiety from medium to mild levels, as found in our study, mirrors the outcomes of similar research, reinforcing the assertion that hypnobirthing is a potent therapeutic approach for mitigating pregnancy-related anxiety (24). This claim is further corroborated by another study that noted a significant transition in pregnant women's anxiety levels from extremely high to normal post a 12-week hypnobirthing regimen, emphasizing the profound psychological benefits of this therapy (25).…”
Section: Discussionsupporting
confidence: 91%
“…Scoping this review uses the Prism-Scr Method to determine scope according to this theme 10 . The scoping review aims to broaden knowledge or information about research activities related to the desired theme and map the literature with the intended topic; it also seeks to synthesize a study 11 . The method is to recognize the scoping review to see the results broadly and in-depth.…”
Section: Methodsmentioning
confidence: 99%